IMPROVING STUDENTS’ LISTENING COMPREHENSION USING THE YOUTUBE EASY ENGLISH CHANNEL - Nabila, Rifda; Bunau, Eusabinus; Wardah, Wardah (Universitas Tanjungpura, 2025)
Listening comprehension is a crucial skill in EFL learning but often becomes a challenge due to limited vocabulary, varied accents, and fast speech. This research aimed to improve students’ listening comprehension by using the YouTube Easy English Channel as a digital learning medium. The study was conducted through Classroom Action Research (CAR) at SMP Negeri 9 Pontianak in the 2024/2025 academic year, involving 30 eighth-grade students. The research was carried out in two cycles consisting of planning, acting, observing, and reflecting. Data were collected using observation checklists, field notes, and listening comprehension tests. The findings revealed that students’ listening ability improved significantly after the implementation of YouTube videos. In Cycle I, the average score was 63, with only 13.33% of students achieving the minimum mastery criterion (KKTP = 78). After refinement in Cycle II, the average score increased to 85.33 and all students passed. The results showed that the Easy English Channel effectively enhanced students’ skills in identifying main ideas, supporting details, moral values, and vocabulary. It can be concluded that integrating YouTube videos into the classroom provides authentic and engaging learning experiences that help students improve their listening comprehension.